1997
DOI: 10.1159/000246025
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Efficacy of Povidone-Iodine against Antiseptic-Resistant Species

Abstract: The bactericidal activity of commonly used antiseptics against clinical isolates was determined. It is noteworthy that povidone-iodine (PVP-I) solution showed high bactericidal activity against all of the test strains after 30 s of exposure. However, in the case of chlorhexidine gluconate (CHG), residual bacteria were observed in most species. Next, acquisition of resistance to antiseptics was examined, and it was found that remarkable increases in MICs were seen for CHG and alkyldiaminoethylglycine hydrochlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 0 publications
1
79
1
4
Order By: Relevance
“…However, Pseudomonas aeruginosa strains exhibiting raised MIC to chlorhexidine have been observed [29] and MRSA strains with decreased susceptibility have been frequently isolated from clinical settings [30,31]. While other studies also reported the development of resistance towards chlorhexidine [32,33], this was not found in the present study. Although a slight increase in the IC 50 was noted, the change was statistically not significant.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, Pseudomonas aeruginosa strains exhibiting raised MIC to chlorhexidine have been observed [29] and MRSA strains with decreased susceptibility have been frequently isolated from clinical settings [30,31]. While other studies also reported the development of resistance towards chlorhexidine [32,33], this was not found in the present study. Although a slight increase in the IC 50 was noted, the change was statistically not significant.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, PVP-iodine shows high bactericidal activity against resistant bacteria strains, e.g. MRSA or Enterococcus faecium [37] and it was shown that it does not induce adaptation in bacteria [32]. In fact the results presented here prove that repeated treatment with PVP-iodine even led to a more susceptible S. aureus strain in vitro.…”
Section: Discussionmentioning
confidence: 63%
“…saliva, which may suppress the antibacterial properties of antiseptics. On the other hand, methicillin-resistant Staphylococcus aureus (MRSA) resistant to chlorhexidine gluconate (CHG) and benzalkonium chloride as well as other bacterial antiseptics have been reported [1,2,3,4,5]. In fact, oral antiseptics are not always effective in killing MRSA colonizing the pharynx in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, solution with 1:10,000 dilution still presents bactericidal activity. 64,65 Potential disadvantages of povidone-iodine solution are tendency for an irritation to the applied site, cytotoxicity and staining of the tissues. Although in some in-vivo and animal studies the cytotoxicity was observed, these results were not confirmed in humans.…”
Section: E Povidone-iodine Solutionmentioning
confidence: 99%